2016
DOI: 10.1002/bit.25942
|View full text |Cite
|
Sign up to set email alerts
|

Engineering and comparison of non‐natural pathways for microbial phenol production

Abstract: The non-renewable petrochemical phenol is used as a precursor to produce numerous fine and commodity chemicals, including various pharmaceuticals and phenolic resins. Microbial phenol biosynthesis has previously been established, stemming from endogenous tyrosine via tyrosine phenol lyase (TPL). TPL, however, suffers from feedback inhibition and equilibrium limitations, both of which contribute to reduced flux through the overall pathway. To address these limitations, two novel and non-natural phenol biosynthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…Munoz et al 72 reported the construction of an E. coli strain with the metabolic capacity for production of L-DOPA from glucose and speculated that the conversion of L-Tyr into L-DOPA catalyzed by HpaBC may be the rate-limiting step. 74 However, the Tpl pathway suffers from feedback inhibition and equilibrium limitations, and thus reduces the flux through the overall pathway. Then the strain was further engineered by a multiplex automated genome engineering (MAGE) method and the final strain, E. coli DOPA-30N, produced 8.67 g L −1 of L-DOPA in 60 h by fed-batch fermentation.…”
Section: Production Of L-tyr Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Munoz et al 72 reported the construction of an E. coli strain with the metabolic capacity for production of L-DOPA from glucose and speculated that the conversion of L-Tyr into L-DOPA catalyzed by HpaBC may be the rate-limiting step. 74 However, the Tpl pathway suffers from feedback inhibition and equilibrium limitations, and thus reduces the flux through the overall pathway. Then the strain was further engineered by a multiplex automated genome engineering (MAGE) method and the final strain, E. coli DOPA-30N, produced 8.67 g L −1 of L-DOPA in 60 h by fed-batch fermentation.…”
Section: Production Of L-tyr Derivativesmentioning
confidence: 99%
“…One is from L-Tyr catalyzed by endogenous tyrosine via tyrosine phenol lyase (Tpl), 58 and the other two are both derived from chorismate via p-hydroxybenzoic acid and salicylic acid biosynthetic pathway, respectively. 74 However, the Tpl pathway suffers from feedback inhibition and equilibrium limitations, and thus reduces the flux through the overall pathway. As the phenol concentration increased in the medium, microbial cell growth was retarded and inhibited.…”
Section: Production Of L-tyr Derivativesmentioning
confidence: 99%
“…In addition, Ren, Yang, Yuan, and Sun () explored the potential of using the third pathway that utilized salicylate as the intermediate and achieved 472 mg/L phenol production using glucose, glycerol and yeast extract as the carbon substrates. Thompson, Machas and Nielsen () compared the phenol biosynthesis using all three pathways and showed that the pathway via salicylate had a higher production yield (35.7 mg/g) than the other two pathways under the analog cultivation conditions. Despite these achievements, further improvement of phenol bioproduction calls for application more sophisticated methodologies.…”
Section: Introductionmentioning
confidence: 99%
“…Microbial production of aromatic chemicals has largely been enabled via pathway engineering, generally consisting of either: (i) the functional reconstruction of naturally‐occurring but non‐native (often plant) pathways; or (ii) the bottom‐up construction of novel pathways comprised of individual enzymes derived from a diversity of heterologous sources. Recent examples include the successful engineering of microbes capable of the de novo production of, in the first case, flavonoids (usually consisting of two phenyl groups and a heterocyclic ring), stilbenes (ethylene moiety with two phenyl groups), and coumarins (containing a 1,2‐benzopyrone backbone), and, in the second case, numerous aromatic aldehydes, alcohols, and acids, styrenics, and phenolics . In most cases, these heterologous pathways stem from natively produced aromatic chemicals such as the aromatic amino acids (i.e.…”
Section: Modular Engineering Strategies For Optimizing Pathway Flux Amentioning
confidence: 99%
“…Recent examples include the successful engineering of microbes capable of the de novo production of, in the first case, flavonoids (usually consisting of two phenyl groups and a heterocyclic ring), 10,11 stilbenes (ethylene moiety with two phenyl groups), 12,13 and coumarins (containing a 1,2-benzopyrone backbone), 14,15 and, in the second case, numerous aromatic aldehydes, alcohols, and acids, [16][17][18][19][20][21] styrenics, [22][23][24][25] and phenolics. [26][27][28][29][30][31][32][33] In most cases, these heterologous pathways stem from natively produced aromatic chemicals such as the aromatic amino acids (i.e. L-phenylalanine, L-tyrosine, and L-tryptophan) or their precursors (e.g.…”
Section: Modular Engineering Strategies For Optimizing Pathway Flux Amentioning
confidence: 99%